2003
DOI: 10.1016/s0378-1097(03)00512-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of species-specific genes using a flexible, web-based querying system

Abstract: We describe a query-based web-accessible system (www.neurogadgets.com/bws.php) for facilitating comparative microbial genomics. A variety of query pages are available, each with numerous options, that allow a biologist to pose relevant questions of genomic data. We illustrate with a characterization of species-specific protein-coding genes (so-called 'ORFans'), finding that they are on average smaller, faster evolving, and less G+C-rich, and that they encode proteins more basic in their predicted isoelectric p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 35 publications
4
33
0
Order By: Relevance
“…Similar to what has been observed for bacteria (Charlebois et al 2003;Daubin et al 2003), the ORFans in Drosophila are short, AT rich, and quickly evolving relative to ancestral genes (Domazet-Loso and Tautz 2003). Unfortunately, the sparse sampling of insect genomes raises the possibility that the ORFans identified in Drosophila include genes that originated recently as well as those lost by (or not detected in) other lineages.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…Similar to what has been observed for bacteria (Charlebois et al 2003;Daubin et al 2003), the ORFans in Drosophila are short, AT rich, and quickly evolving relative to ancestral genes (Domazet-Loso and Tautz 2003). Unfortunately, the sparse sampling of insect genomes raises the possibility that the ORFans identified in Drosophila include genes that originated recently as well as those lost by (or not detected in) other lineages.…”
Section: Discussionsupporting
confidence: 57%
“…Whereas the degenerative or accelerated evolution of ancestral genes can serve as a mechanism for generating ORFans both in bacteria species undergoing genome reduction (Amiri et al 2003) and in eukaryotes (Domazet-Loso and Tautz 2003), the extreme differences in base composition of ORFans and native genes indicate that this is not the case for ORFans in E. coli. Because all bacterial genomes with G+C contents >30% have intergenic regions that are relatively A+T rich, it has also been suggested that ORFans arise from errors in annotating noncoding regions (Charlebois et al 2003). But the fact that most of the intergenic regions are homologous among strains of E. coli indicates that these regions are not the source of unique, strain-specific sequences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We constructed the following six trees with the 147 genomes currently available to us within our genomic analysis system, NGIBWS (7).…”
Section: Methodsmentioning
confidence: 99%